THE EFFECTIVENESS OF LAVENDER AROMATHERAPY IN REDUCING THE LEVEL OF DYSMENORRHEA IN ADOLESCENT GIRLS - Rahayu Savitri; Ovi Hardyanti (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2019)
Dysmenorrhoea is pain during menstruation accompanied by cramps in the lower abdomen that spreads to the back and thighs, the pain usually occurs on the first or second day of menstruation and reaches its peak in the first 24 hours. Lavender Aromatherapy is one of the nonpharmacological therapies to decrease the intensity of dysmenorrhea. The purpose of this research was to determine the effectiveness of lavender aromatherapy in reducing dysmenorrhea in adolescent girls. This research is a quantitative study using a pre-experimental method with One Group Pretest Posttest approach. The purposive sampling technique used in this study, the sample was 34 respondents. Data collection tools used a pain measurement scale and the observation sheet. The data were analyzed using the dependent T-Test with α = 0.05. The results of this research obtained the dysmenorrhea scale before aromatherapy was moderate pain (76.5%) after aroma-therapy reduced become mild pain (55.9%). The T-test found p-value 0.000 < α (0.05). There is an influence of aromatherapy in reducing in the teenagers (girls) Conclusion: There is the influence of aromatherapy in reducing pain scale in the teenagers (girls). Young women can lavender aromatherapy as alternative non-pharmacological therapies to solve dysmenorrhea and advice have active roles in managing their dysmenorrhea.Keywords: Effectiveness, dysmenorrhea, lavender aromatherapy, teenage girls.